Core decompression vs. allogenic non-vascularized bone grafting in patients with osteonecrosis of the femoral head - Mei, Jin; Jiang, Zai-ping; Pang, Li-li; Huang, Yingtao; Gong, Yu; Zhu, Jun; Zhang, Ling-wei (Frontiers in Surgery, 2023)
Background Core decompression and allogenic non-vascularized bone grafting are used in the early stage of osteonecrosis of the femoral head for a period. Since the comparison of the core decompression and allogenic non-vascularized bone grafting are less reported, the purpose of our study was to investigate the difference of two procedures in patients with the osteonecrosis of the femoral head. Methods Between January 2018 and January 2019, 59 patients (64 hips) were divided into core decompression group and non-vascularized bone grafting group according to their procedures. The primary outcomes are visual analog score (VAS) and Harris hip score. Survivorship was analyzed with the collapse of the femoral head or conversion to total hip arthroplasty (THA) as the endpoint. Results At the final follow-up, two hips underwent THA in the core decompression group and three hips in the allogenic non-vascularized bone grafting group. The radiographic survival rates were 76.9% and 77.3%, respectively, in both groups. The VAS of the core decompression group was 6.08 ± 1.164 and 3.30 ± 1.431 before and 2 years after operation (P < 0.05), respectively. The VAS of the allogenic non-vascularized bone grafting group was 6.00 ± 1.209 and 3.15 ± 1.537 before and 2 years after operation (P < 0.05), respectively. The Harris hip score of the core decompression group was 52.49 ± 6.496 before operation, and 2 years after operation, it increased by 81.14 ± 8.548 (P < 0.05); The Harris hip score of allogenic the non-vascularized bone grafting group was 53.56 ± 5.925 and 81.33 ± 7.243 before and 2 years after operation (P < 0.05), respectively. In the core decompression group, body mass index (BMI) >25 kg/m2 was correlated with the collapse of femoral head or conversion to THA [P < 0.05; 95% confidence interval (CI), 0.006–1.334], and Association Research Circulation Osseous (ARCO) III was correlated with the collapse of femoral head or conversion to THA (P < 0.05; 95% CI, 2.514–809.650). In the allogenic non-vascularized bone grafting group, age, BMI, and ARCO stage were significantly associated with the collapse of femoral head or conversion to THA (P > 0.05). Conclusion The clinical survival rate of the femoral head in the core decompression group was slightly better than that in the allogenic non-vascularized bone grafting group. There was no significant difference in the radiographic survival rate of the femoral head between the two groups. Both groups can alleviate pain and improve functional of patients, but there was no significant difference in the degree of improvement. In the core decompression group, BMI >25 kg/m2 and ARCO III correlated with the collapse of femoral head or conversion to THA. In the allogenic non-vascularized bone grafting group, no association was found between age, BMI, and ARCO stage and the collapse of femoral head or conversion to THA. Level of evidence III.